Beyond Determinism: Geography of Jewishness in Nathan Englander’s “Sister Hills” and Michael Chabon’s The Yiddish Policemen’s Union - Filip Boratyn (European Journal of American Studies)
The discourses of modern Jewish statehood have always been entangled with the notion of borders and with the tradition of religiously inspired historical determinism. The Zionist project negotiated between the God-given, predetermined character of the Jewish return to “the Holy Land” and more secular justifications for settlement in the Palestine. Nevertheless, the establishment of the State of Israel relied on a strong assertion of redrawn geographical boundaries, which were symbolically strengthened by the authority of the Biblical geography of Jewishness. This article aims to investigate how two contemporary Jewish American literary texts, Natahan Englander’s “Sister Hills” (2012) and Michael Chabon’s The Yiddish Policemen’s Union (2008), address the stability of Jewish borders in relation to their reliance on the discourses of religious determinism. I argue that while the generic framework of a realist short story and the Israeli setting of “Sister Hills” lead it to examine the essentialism of the Biblical discourse surrounding “the Holy Land,” Chabon’s novel, through its adoption of a more speculative approach, which involves moving the center of Jewish statehood to Alaska, is able to open up the discourse about Jewish territoriality to more postmodern contexts and introduce free will into the geography of Jewishness.